2016
DOI: 10.1140/epjds/s13688-016-0070-8
|View full text |Cite|
|
Sign up to set email alerts
|

Linguistic neighbourhoods: explaining cultural borders on Wikipedia through multilingual co-editing activity

Abstract: In this paper, we study the network of global interconnections between language communities, based on shared co-editing interests of Wikipedia editors, and show that although English is discussed as a potential lingua franca of the digital space, its domination disappears in the network of co-editing similarities, and instead local connections come to the forefront. Out of the hypotheses we explored, bilingualism, linguistic similarity of languages, and shared religion provide the best explanations for the sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 55 publications
(84 reference statements)
2
45
0
Order By: Relevance
“…To gauge similarity in terms of cultural and socio-economic dimensions, we calculate the Euclidean distance between the respective scores given by Hofstede and QoG data. We further add as another aspect the geographical distance between countries, which is computed as the geodesic distance in kilometers between country capitals [19].…”
Section: Country Similarity Computationmentioning
confidence: 99%
“…To gauge similarity in terms of cultural and socio-economic dimensions, we calculate the Euclidean distance between the respective scores given by Hofstede and QoG data. We further add as another aspect the geographical distance between countries, which is computed as the geodesic distance in kilometers between country capitals [19].…”
Section: Country Similarity Computationmentioning
confidence: 99%
“…Unfortunately, this is different in languages other than Spanish, where these pages may not exist. This is a perfect example of the different levels of development that can be found in Wikipedia (Halavais;Lackaff, 2008;Jiménez-Pelayo, 2009;Samoilenko et al, 2016), as content is created according to users' interests, with little coordination.…”
Section: Mapping To Existing Categoriesmentioning
confidence: 99%
“…More than 28 million people have contributed to Wikipedia, and more than 116,000 can be considered active users, meaning they have edited content during the last month. It is, therefore, the biggest multilingual collaborative effort ever made (Samoilenko et al, 2016). In the particular case of the Spanish language edition of Wikipedia, it has more than 1.2 million articles and is the 9 th largest, with more than 15,000 active users in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The study also concluded that language remains a formidable hurdle to the spread of content. Similarly, in [48], cultural borders on Wikipedia through multilingual co-editing activity have been studied, showing that the domination of the English language disappears in the network of co-editing similarities, and that instead local connections come to the forefront. An approach has also been proposed there that allows the extraction of significant cultural borders based on the editing activity of Wikipedia users.…”
Section: Introductionmentioning
confidence: 99%